Aclidinium bromide in fixed-dose combination with formoterol fumarate in the management of COPD: an update on the evidence base. (May 2019) - D'Urzo, Anthony D.; Singh, Dave; Donohue, James F.; Chapman, Kenneth R.
Aclidinium bromide/formoterol fumarate (AB/FF) 400/12 µg is a twice-daily long-acting muscarinic receptor antagonist and long-acting β2 agonist (LAMA/LABA) dual-bronchodilator maintenance therapy used to relieve symptoms and reduce future risk of exacerbations in adults with chronic obstructive pulmonary disease (COPD). To date, there have been several clinical studies and post hoc analyses of AB/FF, assessing treatment outcomes in patients with moderate-to-severe COPD. These studies have looked at a range of outcomes, including lung function parameters, patient-reported symptom scores, quality-of-life measures assessing impaired health and perceived well-being, and the frequency, duration, and severity of exacerbations. In light of the major 2017 revision to the Global initiative for chronic Obstructive Lung Disease (GOLD) recommendations, and the subsequent updates, we present an update on the latest evidence supporting the efficacy and safety of AB/FF. This review discusses the clinical relevance of the improvements in lung function, symptoms, quality of life, and exacerbations in patients with COPD reported in the phase III and IV trials of AB/FF. Given the current concerns over unnecessary inhaled corticosteroid (ICS) use in COPD, we also touch briefly on the use of blood eosinophils as a biomarker for identifying those patients with COPD already using LAMA/LABA therapy for whom the addition of ICS might be of benefit.